Method for preparing self-supporting light material and application
By preparing TiN@AlN core-shell particles and benzoxazole epoxy resin composite materials, the shortcomings of traditional materials in terms of thermal conductivity, mechanical properties and expansion have been overcome. This has resulted in a self-supporting lightweight material with high thermal conductivity, low expansion, light weight and insulation, which is suitable for electronic devices and aerospace fields.
Patent Information
- Application Number
- CN202511034557.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2025-10-31
- Estimated Expiration
- 2045-07-25
AI Technical Summary
Existing materials cannot simultaneously meet the comprehensive requirements of high thermal conductivity, low expansion, and high mechanical properties. Traditional polymer-based composite materials have insufficient thermal conductivity, metal-based materials have high density and poor corrosion resistance, and ceramic-based materials are brittle and difficult to process.
A self-supporting lightweight material was prepared by injection molding using a prepolymer of TiN@AlN core-shell particles mixed with benzoxazole and epoxy resin to form a continuous thermal conductivity network. The interfacial bonding force and molding process were optimized by combining compatibilizers and accelerators.
It achieves high thermal conductivity, low coefficient of thermal expansion, excellent mechanical properties and insulation, and is suitable for electronic devices and aerospace applications. The material is dense and lightweight.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lightweight materials technology, specifically relating to methods for preparing self-supporting lightweight materials and their applications. Background Technology
[0002] With the rapid development of electronic devices, aerospace and new energy fields, higher requirements are placed on material performance: on the one hand, the trend of miniaturization and integration of electronic devices has led to a surge in heat dissipation demand, and traditional polymer-based composite materials are prone to thermal failure due to insufficient thermal conductivity; on the other hand, extreme environments pose severe challenges to the mechanical strength and thermal stability of materials.
[0003] In the existing technology, although metal-based thermal conductive materials have excellent thermal conductivity, they have high density and poor corrosion resistance; although ceramic-based materials have high temperature resistance and low expansion, they are brittle and difficult to process; although polymer-based composite materials are lightweight, they have insufficient thermal conductivity and weak interfacial bonding with inorganic fillers, making it difficult to simultaneously meet the comprehensive requirements of high thermal conductivity, low expansion and high mechanical properties. Summary of the Invention
[0004] The first objective of this invention is to provide a method for preparing a self-supporting lightweight material. The second objective of this invention is to provide an application of the method for preparing a self-supporting lightweight material.
[0005] To achieve the above and other related objectives, the present invention provides the following technical solutions: A method for preparing self-supporting lightweight materials includes the following steps: Thermally conductive core-shell particles, prepolymer, and compatibilizer are mixed and stirred; curing agent and accelerator are added, and vacuum degassing is performed; the degassed mixture is loaded into an injection molding barrel; injection molding is performed, and the material is demolded to obtain a self-supporting lightweight material. The thermally conductive core-shell particles include TiN@AlN particles coated with AlN, and the prepolymer includes a prepolymer of benzoxazole and epoxy resin.
[0006] Furthermore, the preparation method of TiN@AlN particles includes the following steps: TiO2 hollow spheres were immersed in a glucose aqueous solution, stirred, centrifuged, and dried to obtain pretreated TiO2 hollow spheres. In an ammonia atmosphere, pretreated TiO2 hollow spheres are heated to 800-1200℃ and held at that temperature to obtain TiN hollow spheres. After cooling, the residue is removed, the spheres are washed, and dried for later use. TiN hollow spheres were ultrasonically dispersed in anhydrous ethanol; aluminum triethoxy was added; the pH was adjusted to 4-5; the mixture was stirred, and centrifuged after the reaction; the precipitate was vacuum dried; the precipitate was dried, calcined, and cooled to obtain TiN@AlN particles.
[0007] Furthermore, the particle size of the TiO2 hollow spheres is 0.8-1.5μm; the calcination process is as follows: after drying, calcination is carried out at 400-600℃ for 1-2 hours under nitrogen protection, followed by heating to 800-1200℃ and holding for 2-4 hours.
[0008] It should be noted that, using the above technical solution, hollow TiO2 spheres are used as a precursor. Through carbothermic reduction and calcination in an ammonia atmosphere, hollow TiN spheres are obtained, forming a core with excellent thermal conductivity. A uniform coating layer is formed through the hydrolysis and condensation reaction of aluminum triethoxy on the TiN surface. After calcination, this coating layer transforms into a dense AlN shell, thus constructing TiN@AlN core-shell structured particles. The AlN shell possesses high thermal conductivity, moderate surface energy, and strong stability, maintaining the overall thermal conductivity of the particles while enhancing the physical and chemical bonding ability with the resin matrix in later stages.
[0009] Furthermore, the preparation method of the prepolymer of benzoxazole mixed with epoxy resin includes the following steps: DAB and BTDA are dissolved in NMP, heated to 160-200℃, and reacted at this temperature. After the reaction, a catalyst is added, and the temperature is raised to 200-240℃. After holding at this temperature for 1-3 hours, the mixture is cooled to obtain a benzoxazole prepolymer solution. Epoxy resin is added after cooling and stirred to disperse the solution. The mixture is then heated to 80-120℃ and stirred for 2-6 hours. After the reaction, the mixture is cooled to obtain the prepolymer.
[0010] Furthermore, the mass ratio of the benzoxazole prepolymer solution to the epoxy resin is 1:1-3; the catalyst includes sodium benzenesulfonate.
[0011] It should be noted that, using the above technical solution, DAB and BTDA react in NMP to form a linear polyamic acid structure, and a prepolymer containing a benzoxazole ring structure is obtained through a ring-closing reaction, which has high modulus and thermal stability; the benzoxazole prepolymer is blended with epoxy resin to form an interpenetrating network structure, which can improve the toughness and thermomechanical stability of the system.
[0012] Furthermore, the curing agent includes phenolic curing agent, the compatibilizer includes styrene maleic anhydride, and the accelerator includes epoxy accelerator.
[0013] It should be noted that by adopting the above technical solution and adding compatibilizers and accelerators, the dispersibility and curing rate of the filler are further enhanced.
[0014] Furthermore, the parameters for injection molding include: using injection molding equipment, setting the mold temperature to 150-190℃, the injection pressure to 40-60MPa, and the injection time to 10-50s; and curing at 160-200℃ for 1-3 hours after holding pressure in the mold.
[0015] It should be noted that, using the above technical solution, during the injection molding process, the thermally conductive core-shell particles are uniformly distributed in the prepolymer matrix to form a continuous thermal conduction network; the synergistic effect of the curing agent and the accelerator enables the system to cure rapidly and construct a dense three-dimensional structure; after molding, the composite material simultaneously possesses high thermal conductivity, self-supporting mechanical properties, and thermal stability, making it suitable for applications with high requirements for both thermal conduction and mechanical properties.
[0016] It should be further explained that the difficulties successfully solved by injection molding in this invention are: 1) Insufficient compatibility: TiN@AlN core-shell particles are inorganic ceramic phases (high hardness, strong surface inertness), while the prepolymer of benzoxazole and epoxy resin is an organic polymer phase (low polarity, flexible chain segments). The surface energy difference between the two is large, which easily leads to an imbalance of "agglomeration-dispersion". If the compatibilizer does not sufficiently modify the surface of the ceramic particles (e.g., maleic anhydride groups are not completely anchored to the hydroxyl groups on the ceramic surface), or if the dispersion process (e.g., insufficient ultrasonic dispersion time) does not eliminate the van der Waals forces between particles, ceramic particles are prone to agglomeration during injection, resulting in excessively high local filler concentration. After curing, stress concentration points are formed, reducing the material's structural density and mechanical properties (e.g., compressive strength). 2) Weak interfacial bonding: The surface energy of ceramic particles is much lower than that of the polymer matrix. If effective chemical bonds (such as Ti-OC or Al-OC covalent bonds) or physical anchoring (such as hydrogen bonds) are not formed at the interface, the high shear force during injection will cause the particles to peel off from the polymer interface, forming "voids" or "weak interfacial layers". Ultimately, microcracks will appear inside the material, reducing thermal conductivity continuity (TiN / AlN thermal conductivity network breakage) and mechanical strength. 3) Although BOZ-EP prepolymer has a certain fluidity at a certain temperature, the viscosity of the material will increase significantly after mixing with TiN@AlN particles. During injection, high-viscosity material needs to be pushed under high pressure to quickly fill the mold cavity. If the pressure is insufficient or the injection speed is too slow, it is easy to cause "short shot" (the cavity is not filled). If the pressure is too high or the speed is too fast, the ceramic particles may break due to shearing, destroying the integrity of the core-shell structure and reducing thermal conductivity. For example, after the AlN coating layer breaks, TiN comes into contact with air, and the interfacial thermal resistance increases. 4) The mold temperature setting must simultaneously meet the following requirements: the prepolymer must be in a viscous flow state to facilitate injection filling; premature BOZ closure should be avoided to prevent some side reactions, such as incomplete dehydration and cyclization of polyamic acid, or premature curing of epoxy resin, which would cause a sudden increase in material viscosity during injection and prevent flow. 5) Pressure setting: The curing rate must be controlled during the in-mold holding pressure stage to avoid local overheating due to an excessively steep exothermic peak of the prepolymer, which could lead to AlN decomposition and reduce the thermal stability of the material.
[0017] The second objective of this invention is to provide the self-supporting lightweight material as a sacrificial layer in a chip structure, wherein the self-supporting lightweight material is prepared according to the method for preparing the self-supporting lightweight material.
[0018] It should be noted that no metal substrate is used in the raw materials of this invention, and the resulting self-supporting lightweight material has insulation properties, which can be better applied to chip structures.
[0019] Furthermore, the sacrificial layer includes a temporary base.
[0020] Furthermore, the chip structure fabrication method includes the following steps: using a chip mounter to attach the chip to a self-supporting lightweight material with an adhesive, thereby forming a three-layer structure consisting of a chip, an adhesive, and a self-supporting lightweight material.
[0021] This invention, through the synergistic application of core-shell structure design, polymer matrix optimization, and composite molding process, produces a self-supporting lightweight material with significantly improved overall performance. Specific beneficial effects are as follows: 1. High thermal conductivity: Both TiN and AlN in the core-shell structure are high thermal conductivity materials. They form a continuous interface through hydrolysis and condensation, which effectively reduces the interfacial thermal resistance. Combined with the blending modification of benzoxazole prepolymer and epoxy resin, the rigid benzoxazole ring of benzoxazole prepolymer can improve the mobility of polymer chain segments. In the end, the thermal conductivity of the composite material is better than that of traditional polymer-based materials.
[0022] 2. Low coefficient of thermal expansion: Both TiN and AlN are materials with low coefficients of thermal expansion. Combined with the synergistic effect of the rigid benzoxazole ring and epoxy resin, the overall coefficient of thermal expansion of the material is as low as 12ppm / ℃, which is highly matched with the coefficient of thermal expansion of electronic components (such as silicon chips), and can effectively avoid interface failure caused by thermal stress.
[0023] 3. Excellent mechanical properties: Both TiN and AlN are high-modulus materials. The TiN@AlN core-shell particles prepared by both have high modulus. Their synergistic effect with the rigid benzoxazole prepolymer, combined with the compatibilizer to enhance the filler-polymer interface, can reduce interface defects and make the material compressive strength as high as 160MPa, far exceeding that of ordinary polymer-based composite materials with a strength of less than 50MPa.
[0024] 4. Dense structure: Both TiN and AlN are low-density materials. Combined with injection molding process, the materials are densified, and the final material achieves lightweight while maintaining high strength. It is suitable for weight-sensitive fields, such as aerospace or electronics.
[0025] 5. Wide Range of Applications: Traditional high thermal conductivity materials (such as metal-based materials) are often unsuitable for direct use in applications requiring insulation due to their high electrical conductivity. The self-supporting lightweight material prepared in this invention not only possesses high thermal conductivity, low expansion, and high strength, but also exhibits excellent insulation properties. The prepolymer is a blend of benzoxazole and epoxy resin, both of which are insulating materials. Although TiN itself has a certain degree of conductivity, the TiN core is completely encapsulated by the AlN shell, forming a core-shell structure of "conductive core-insulating shell." Even if the TiN core is partially exposed (e.g., due to interface defects), the AlN shell can still hinder the migration of charge carriers between the filler and the matrix through the "steric hindrance" effect, preventing the formation of continuous conductive pathways. The polar groups of the prepolymer (such as ether bonds and hydroxyl groups) and the hydroxyl groups on the TiN@AlN surface form a dipole layer at the interface, generating interfacial polarization charges (bound charges), further hindering the migration of free charge carriers. While compatibilizers enhance the interfacial bonding between the filler and the matrix, the covalent bonds formed by their anhydride groups and the polymer's ester bonds are weak bonds. Electrons must cross these bonds to migrate, further increasing the interfacial resistance. Therefore, the insulating properties of the material in this invention give it greater application value in electronic packaging and power electronic devices. Detailed Implementation
[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0027] Unless otherwise specified, the equipment and materials used in the embodiments can be readily obtained from commercial companies.
[0028] Example 1 The specific steps for preparing thermally conductive core-shell particles are as follows: TiO2 hollow spheres were immersed in a 20wt% glucose aqueous solution, stirred for 2 hours, centrifuged, and dried at 80℃ to obtain pretreated TiO2 hollow spheres.
[0029] In an ammonia atmosphere, pretreated TiO2 hollow spheres were heated to 1000℃ at a rate of 5℃ / min and held at that temperature for 4 hours to obtain TiN hollow spheres. After cooling, the spheres were soaked in dilute nitric acid to remove residues, washed with deionized water, and dried for later use.
[0030] 1.0 g of TiN hollow spheres were ultrasonically dispersed in 30 mL of anhydrous ethanol; 1 mmol of aluminum triethoxy was added; glacial acetic acid was added dropwise to adjust the pH to 4-5; and the mixture was stirred at room temperature for 8 hours to promote the hydrolysis and condensation of aluminum triethoxy on the TiN surface.
[0031] The reaction solution was centrifuged and the supernatant was discarded. The precipitate was transferred to a vacuum drying oven and dried at 60°C and -0.08 MPa for 12 hours. After drying, it was calcined at 500°C for 1 hour under nitrogen protection, then heated to 1000°C and held for 2 hours to complete the conversion of aluminum triethoxy to AlN. After cooling, thermally conductive core-shell particles were obtained, which were core-shell structured TiN@AlN particles, with TiN coated by AlN.
[0032] The above-mentioned raw material information includes: TiO2 hollow spheres with a particle size of 1.5μm, which can be purchased from Xi'an Qiyue Biotechnology.
[0033] Example 2 The specific steps for synthesizing the prepolymer are as follows: 212g DAB and 266g BTDA were added to a three-necked flask and dissolved in 100mL NMP. The mixture was heated to 180℃ and kept at this temperature for 6 hours to form the intermediate polyamic acid. Then, 0.5g sodium benzenesulfonate was added as a catalyst and the temperature was slowly increased to 220℃ to close the ring and form a benzoxazole structure. After keeping at this temperature for 2 hours, the mixture was cooled to obtain a benzoxazole prepolymer solution.
[0034] The benzoxazole prepolymer solution was cooled to 80°C; epoxy resin E51 was added, with a mass ratio of benzoxazole prepolymer solution to epoxy resin E51 of 1:1.5, and the mixture was stirred and dispersed thoroughly; the mixture was heated to 100°C and stirred for 4 hours to form a stable blend; after cooling to 60°C, the BOZ-EP prepolymer was obtained.
[0035] The above raw material information includes: DAB: 3,3'-Diaminobenzidine, BR grade. BTDA: 3,3',4,4'-Benzophenone tetracarboxylic dianhydride. NMP: Solvent, N-methylpyrrolidone.
[0036] Example 3 The materials prepared in Examples 1 and 2 were used as raw materials to further prepare self-supporting lightweight materials. The specific steps are as follows: By weight, 150 parts of thermally conductive core-shell particles, 100 parts of prepolymer, and 10 parts of compatibilizer are mixed and stirred evenly at 100°C; 15 parts of curing agent and 1.5 parts of accelerator are added, and the mixture is degassed under vacuum; the degassed mixture is loaded into an injection molding barrel; an injection molding machine is used, with the mold temperature set at 170°C, the injection pressure at 50MPa, and the injection time at 30s; after holding pressure in the mold, it is cured at 180°C for 2 hours; after demolding, a dense, self-supporting lightweight material is obtained.
[0037] The above raw material information includes: the curing agent is a phenolic curing agent; the compatibilizer is styrene-maleic anhydride, SMA1000 can be selected; and the accelerator is DMP-30 (2,4,6-tris(dimethylaminomethyl)phenol).
[0038] Self-supporting lightweight materials can be used in chip fabrication. For example, they can be used as sacrificial layers in chip structures. As is known, a sacrificial layer is a special material layer used in micro- and nano-fabrication processes. Its main function is to provide necessary structural support or serve as a temporary substrate at a certain stage of device fabrication, and then it is intentionally removed in subsequent steps to release or form the desired structure.
[0039] Its main functions are: 1) Structural support: In the manufacturing process of multi-layer structures, the sacrificial layer can serve as a temporary support structure to help form the superstructure. 2) Space maintenance: When forming cavities or channels, the sacrificial layer can maintain the required space and ensure the integrity of the structure.
[0040] The coefficient of thermal expansion (CTE) of the self-supporting lightweight material in Example 3 was tested at 25-200°C using the ASTM E831 Thermomechanical Analyzer (TMA) method.
[0041] The compressive strength of the self-supporting lightweight material in Example 3 was tested according to GB / T 1041-2008 using a universal testing machine. The sample size was 10mm×10mm×10mm.
[0042] Results: The compressive strength of the self-supporting lightweight material in Example 3 was 160 MPa, and the coefficient of thermal expansion was 12 ppm / ℃.
[0043] The coefficient of thermal expansion of the self-supporting lightweight material prepared by this invention is close to that of the BT substrate in the prior art, and significantly lower than that of the CTE substrate.
[0044] Example 4 The sacrificial layer includes a temporary substrate, and the specific application method is as follows: A self-supporting lightweight material is used as a temporary substrate. A chip is then attached to the self-supporting lightweight material using an adhesive layer, forming a three-layer structure consisting of the chip, adhesive, and self-supporting lightweight material. Subsequently, the adhesive is dissolved to separate the chip from the self-supporting lightweight material. The adhesive used is a standard chip adhesive.
[0045] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a self-supporting lightweight material, characterized in that, Includes the following steps: Thermally conductive core-shell particles, prepolymer, and compatibilizer are mixed and stirred; curing agent and accelerator are added, and vacuum degassing is performed; the degassed mixture is loaded into an injection molding barrel; injection molding is performed, and the material is demolded to obtain a self-supporting lightweight material. The thermally conductive core-shell particles include TiN@AlN particles coated with AlN, and the prepolymer includes a prepolymer of benzoxazole and epoxy resin.
2. The method for preparing a self-supporting lightweight material according to claim 1, characterized in that, The preparation method of TiN@AlN particles includes the following steps: TiO2 hollow spheres were immersed in a glucose aqueous solution, stirred, centrifuged, and dried to obtain pretreated TiO2 hollow spheres. In an ammonia atmosphere, pretreated TiO2 hollow spheres are heated to 800-1200℃ and held at that temperature to obtain TiN hollow spheres. After cooling, the residue is removed, the spheres are washed, and dried for later use. TiN hollow spheres were ultrasonically dispersed in anhydrous ethanol; aluminum triethoxy was added; the pH was adjusted to 4-5; the mixture was stirred, and centrifuged after the reaction; the precipitate was vacuum dried; the precipitate was dried, calcined, and cooled to obtain TiN@AlN particles.
3. The method for preparing self-supporting lightweight materials according to claim 2, characterized in that, The particle size of TiO2 hollow spheres is 0.8-1.5μm; the calcination process is as follows: after drying, calcinate at 400-600℃ for 1-2 hours under nitrogen protection, then raise the temperature to 800-1200℃ and hold for 2-4 hours.
4. The method for preparing a self-supporting lightweight material according to claim 1, characterized in that, The preparation method of the prepolymer of benzoxazole mixed with epoxy resin includes the following steps: DAB and BTDA are dissolved in NMP, heated to 160-200℃, and reacted at this temperature. After the reaction, a catalyst is added, and the temperature is raised to 200-240℃. After holding at this temperature for 1-3 hours, the mixture is cooled to obtain a benzoxazole prepolymer solution. Epoxy resin is added after cooling and stirred to disperse the solution. The mixture is then heated to 80-120℃ and stirred for 2-6 hours. After the reaction, the mixture is cooled to obtain the prepolymer.
5. The method for preparing a self-supporting lightweight material according to claim 4, characterized in that, The mass ratio of benzoxazole prepolymer solution to epoxy resin is 1:1-3; the catalyst includes sodium benzenesulfonate.
6. The method for preparing a self-supporting lightweight material according to claim 1, characterized in that, The curing agent includes phenolic curing agent, the compatibilizer includes styrene-maleic anhydride, and the accelerator includes epoxy accelerator.
7. The method for preparing a self-supporting lightweight material according to claim 1, characterized in that, The parameters for injection molding include: using injection molding equipment, setting the mold temperature to 150-190℃, the injection pressure to 40-60MPa, and the injection time to 10-50s; and curing at 160-200℃ for 1-3 hours after holding pressure in the mold.
8. A self-supporting lightweight material is used in chip structures, characterized in that, The self-supporting lightweight material is used as a sacrificial layer in the chip structure and is prepared by the method for preparing self-supporting lightweight material according to any one of claims 1-7.
9. The self-supporting lightweight material according to claim 8 is applied to a chip structure, characterized in that, The sacrificial layer includes a temporary substrate.
10. The self-supporting lightweight material according to claim 8 is applied to a chip structure, characterized in that, The chip structure fabrication method includes the following steps: using a chip mounter to attach the chip to a self-supporting lightweight material with an adhesive, thereby forming a three-layer structure consisting of a chip, an adhesive, and a self-supporting lightweight material.
Citation Information
Patent Citations
Heat-conducting plastic and preparation method thereof
CN102746560A
High-thermal-conduction adhesive
CN105694787A
Heat-conducting and insulating epoxy resin composite material as well as preparation method and application thereof
CN114836004A
Thermally conductive materials based on thermally conductive hollow particles and fabrication method thereof
KR1020130041554A